Assessing risk of clogging in community scale managed aquifer recharge sites for drinking water in the coastal plain of south-west Bangladesh - Sultana, Sarmin; Ahmed, Kazi Matin (Bangladesh Journal of Scientific Research, 2016)
Community scale managed aquifer recharge (MAR) has been implemented by infiltrating pond and rooftop rainwater into shallow, locally confined brackish aquifers in the southern deltaic plains of Bangladesh for providing safe drinking water. This paper mainly deals with the risks of physical clogging and the issues of clogging related to aquifer material, design, drilling and construction methods at 20 sites. Risk of chemical and biochemical clogging has also been briefly discussed. High turbidity in the source pond water is mainly responsible for physical clogging. In order to reduce the turbidity MAR system has been designed with an over ground double chambered filtration tank with a graded sand filter in one chamber. Pond water is pumped into the filtration tank to pass through sand filter. Efficiency of turbidity removal is assessed by measuring turbidity of water at the source pond, after passing though the sand filter and at the abstraction well. The turbidity of source (pond) water ranges from 50 to 150 NTU decreases to 5 NTU after passing through the sand filter in most of the sites. Clogging is assessed by performing falling head tests at each recharge well at number of times during the operation of the test sites. A maximum infiltration rate of 6m3/day has been achieved at a number of sites where the average is about 3m3/day. Relatively high nutrient content present both in source and groundwater water could cause biological clogging. Probability of clogging due to clay swelling should be considered due to salinity difference of source and groundwater although sodium adsorption ratio has been observed to be reduced which reduce the risk of reduction of permeability. There is possibility of chemical plugging in the aquifer and around the well from the precipitation of iron bearing minerals as iron concentration has been observed to be reduced. Bangladesh J. Sci. Res. 27(1): 75-86, June-2014